STUDI KELAYAKAN EKONOMI BUDIDAYA DURIAN (Durio zibethinus Murr) RAKYAT DI DESA LAU BAGOT, KECAMATAN TIGALINGGA, KABUPATEN DAIRI - Tabita Wana Imelda L. Gaol; Agus Purwoko; Oding Affandi (Program studi Kehutanan USU, 2015)
Durian is a non-timber forest products, in addition to having ecological value, Durian also has economic value that can be used to increase people incomes. Therefore, this study aimed to determine the feasibility of durian cultivation in Lau Bagot Village, Subdistrict of Tigalingga, District of Dairi. The analytical method used is descriptive analysis and economic feasibility analysis with multiple criteria: Net Present Value (NPV), Benefit Cost Ratio (BCR), and Internal Rate of Returns (IRR) and payback period (PBP). The results showed that the pattern of durian cultivation in this village is done with traditional way and the uneven distribution of trees with density 46 trees/ha. Retrieved NPV Rp 52.981.031/Ha , BCR 2,34 , 24,22 % IRR and PBP 11 years with the prevailing interest rate is 12%. Based on the obtained value of durian cultivation in this village deserves to be developed. Factors that lead to decreased production of durian in Lau Bagot Village is the public perception of the high price of wood has to offer to the public about Rp 500.000/m3, pests and diseases, limited land, and natural disaster, thus preferring to cut down on the selling of fruit.Keywords : durian cultivation, economic feasibility, Desa Lau Bargot